2013
DOI: 10.1124/dmd.113.054874
|View full text |Cite
|
Sign up to set email alerts
|

CPY3A4-Mediated α-Hydroxyaldehyde Formation in Saquinavir Metabolism

Abstract: Saquinavir (SQV) is a protease inhibitor widely used for the treatment of human immunodeficiency virus (HIV) infection. We profiled SQV metabolism in mice using a metabolomic approach. Thirty SQV metabolites were identified in mouse feces and urine, of which 20 are novel. Most metabolites observed in mice were recapitulated in human liver microsomes. Among these novel metabolites, one a-hydroxyaldehyde produced from SQV N-dealkylation was noted and verified for the first time. Meanwhile, the corresponding prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Therefore, the results were strongly empirical and dependent on the investigator’s level of knowledge. However, metabolomics-guided drug metabolism studies have not focused on specific metabolic pathways; therefore, this non-targeted approach facilitates the identification of novel metabolites, the characterization of metabolic enzymes, and the profiling of reactive metabolites [32,36,37,38,39,40,41,42]. This approach is complementary to conventional drug metabolism studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the results were strongly empirical and dependent on the investigator’s level of knowledge. However, metabolomics-guided drug metabolism studies have not focused on specific metabolic pathways; therefore, this non-targeted approach facilitates the identification of novel metabolites, the characterization of metabolic enzymes, and the profiling of reactive metabolites [32,36,37,38,39,40,41,42]. This approach is complementary to conventional drug metabolism studies.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the metabolic pathways of DLX in human liver microsomes (HLM) /mouse liver microsomes (MLM) and mice using liquid chromatography mass spectrometry (LC-MS)-based metabolomic approaches. Our previous studies demonstrated that LC-MS-based metabolomics is a rapid and effective approach to investigate drug metabolism ( Li et al, 2018 ; Li et al, 2020 ), bioactivation ( Li et al, 2011b ; Li et al, 2014 ; Liu et al, 2015 ; Liu et al, 2016 ; MacKenzie et al, 2020 ), and toxicity (O'Connell and Watkins, 2010; Li et al, 2013 ; Lu et al, 2019 ; Zhao et al, 2019 ). Here, a total of 39 metabolites generated from DLX were identified, of which 13 metabolites are novel.…”
Section: Introductionmentioning
confidence: 99%
“…Drugs containing the benzylic carbon motif are prone to be oxidized to its corresponding benzylic alcohol (Mamidi et al, 2014;Ryu et al, 2014) and/or further to the end-product carboxylic acids in vivo (Hvenegaard et al, 2012;Walles et al, 2013;Pozo et al, 2015). It is recognized that there is an aldehyde intermediate in metabolic processing from alcohol to carboxylic acid, and some in vitro trapping tests with methoxyamine or semicarbazide also provided convincing evidence (Li et al, 2014;Inoue et al, 2015;Liu et al, 2015). However, further metabolism of aldehyde intermediates is rarely reported in publications.…”
Section: Discussionmentioning
confidence: 99%